Palm Oil as a Renewable Energy Source: A Study of Indonesia’s Strategy In Overcoming Negative Palm Oil Campaigns - Mella Syaftiani; Eko Priyo Purnomo; Suchanart Singhapat; Moch. Rifqi Mei Redha; Tiara Khirunnisa (Jurnal Ilmu Pemerintahan : Kajian Ilmu Pemerintahan dan Politik Daerah, 2025)
Palm oil is one of the largest renewable energy sources in Indonesia in terms of export production. Negative campaigns conducted by international organizations and other countries have hampered Indonesia's palm oil exports. This study aims to analyze Indonesia's strategy in overcoming negative campaigns against Indonesian palm oil. This study uses a qualitative approach with secondary data from media related to negative campaigns against Indonesian palm oil. The results show that Indonesia's strategy in overcoming negative campaigns, mainly through the expansion of the Indonesian Sustainable Palm Oil Initiative (ISPO) and the Sustainable Palm Oil Forum, involves international diplomacy and technological innovation in converting palm oil into environmentally friendly renewable energy. The analysis contributes to the conclusion that the government can implement sustainable strategies that constitute diplomatic measures in renewable energy technological innovation. Thus, Indonesia has a great opportunity to support the global energy transition by reducing carbon emissions more effectively.